Analisis Pelaksanaan Tank Cleaning Pergantian Muatan dari MTBE ke JET A-1 di Kapal MT. GT EQUALITY - Ahmad Sugiono; Supangat; Djamaludin Malik (KAMPUS AKADEMIK PUBLISING, 2026)
The changeover of cargo from methyl tert-butyl ether (MTBE) to aviation turbine fuel JET A-1 on product and chemical oil tankers requires stringent tank readiness, as JET A-1 is sensitive to hydrocarbon residues, water, salts, and foreign particles. This study aims to analyze the implementation of tank cleaning during the cargo changeover from MTBE to JET A-1 aboard MT. GT EQUALITY and to identify the factors determining the effectiveness of the process. The research employs a qualitative descriptive approach. Data were obtained through direct observation, interviews with crew members, field notes, and documentation during the period from 2 August 2024 to 2 July 2025, with the main focus on activities on 26 January 2025. Data analysis was conducted through data reduction, data presentation, and conclusion drawing and verification. The results show that tank cleaning refers to the Tank Cleaning Guide code C, which includes washing using seawater at normal temperature for 40 minutes, seawater at 50–55°C for 60 minutes, fresh water rinsing for 20 minutes, draining, gas freeing, mopping, drying, initial inspection, corrective actions, wall wash test, tank inspection, and issuance of the Dry Certificate. The initial inspection still found thin residue, internal pipe moisture, water pooling at the bellmouth, residual water on the tank bottom, and a faint MTBE odor. These discrepancies were addressed through local washing, re-drying, and extended gas freeing duration. The final results showed O₂ at 20.9%, H₂S at 0 ppm, a clear hydrocarbon test, chloride test below 2 ppm, and a permanganate test of 58 minutes. Thus, the effectiveness of tank cleaning is determined by procedural accuracy, equipment readiness, crew competence, physical tank condition, supervision, and the application of occupational safety.